KAJIAN NON FINANSIAL TERHADAP KELAYAKAN PENGEMBANGAN USAHA PENANGKARAN BIBIT KELAPA SAWIT BERSERTIFIKAT DI KABUPATEN BANYUASIN - Elisa Wildayana; Muhammad Naufal Elmuttaqin; Dessy Adriani (Fakultas Pertanian Universitas Mataram, 2025)
This study aims to analyze the non-financial feasibility of CV Gotama's certified oil palm seedling nursery business in Banyuasin Regency, South Sumatra. The issue raised in this study is the importance of a comprehensive assessment of the nursery business, not only from a financial perspective, but also from technical, legal, market and marketing, socio-economic, and environmental aspects. This study employs a qualitative descriptive method with a case study approach, supported by primary and secondary data analyzed systematically. The findings indicate that the technical aspects align with operational standards for oil palm seedling production, utilizing production facilities and high-quality seed sources. Legal aspects are fulfilled through business legality, permits, and compliance with labor regulations. The market aspect shows high demand and modern digital-based marketing. From a socio-economic perspective, the company contributes to job creation and the improvement of the village economy. From an environmental perspective, the company applies sustainability principles and responsible waste management. Based on these results, the seedling nursery business operated by CV. Gotama is deemed financially viable and has the potential for long-term sustainability.